2017
DOI: 10.4103/1735-5362.213979
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting liposomes particle size prepared by ethanol injection method

Abstract: Ethanol injection is one of the techniques frequently used to produce liposomes which favors both simplicity and safety. In this process, an ethanolic solution of lipids is rapidly injected into an aqueous medium through a needle, dispersing the phospholipids throughout the medium and promoting the vesicle formation. Being a critical parameter that determines the fate of liposome and its distribution, we studied different factors affecting the particle size of liposomes including different phospholipid (Phosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(77 citation statements)
references
References 15 publications
(20 reference statements)
4
66
1
Order By: Relevance
“…The particle size of liposomal preparation of B 12 (C5) (13.50 mM, PC) was in the range of 139‐151 nm with an average polydespersity index (PDI) of ∼ 38% and average molecular weight of ∼ 310 MDa (Figure left panel). It was found that the variation in lipid content results in variation in the size of liposomes as observed by previous workers …”
Section: Resultssupporting
confidence: 69%
“…The particle size of liposomal preparation of B 12 (C5) (13.50 mM, PC) was in the range of 139‐151 nm with an average polydespersity index (PDI) of ∼ 38% and average molecular weight of ∼ 310 MDa (Figure left panel). It was found that the variation in lipid content results in variation in the size of liposomes as observed by previous workers …”
Section: Resultssupporting
confidence: 69%
“…Two cholesterol: non-ionic surfactant molar ratios were tested (1:1 and 2:1) to study their effect on the physicochemical properties of niosomes. Ethanol injection technique was adopted due to its well-ascribed simplicity and safety [37]. Among different utilized organic solvents, ethanol was found to be a good solvent for niosomes components, including quercetin, avoiding any aggregation during preparation.…”
Section: Resultsmentioning
confidence: 99%
“…From the DLS measurements, the mean hydrodynamic diameter of the nanoparticles was estimated to be 150 nm for Hep-Chl-1 prodrug, 210 nm for Hep-Chl-2 prodrug, and 300 nm for Hep-Chl-3 prodrug (Figure 4c). As the concentration of Chl increased, more Chl molecules were distributed in the prodrug bilayer, resulting in an increase in the particle size [34]. The size of each prodrug nanoparticle determined from AFM data was smaller than that from the DLS data [21,35].…”
Section: Formation Of the Self-assembled Prodrugmentioning
confidence: 86%